Agri-voltaic system: crop production and photovoltaic-based electricity generation from a single land unit - Santra, P.; Singh, R. K.; Meena, H. M.; Kumawat, R. N; Mishra, D.; Jain, D.; Yadav, O. P. (Indian Farming, 2018)
Agri-voltaic system is designed anddeveloped at Central Arid ZoneResearch Institute, Jodhpur throughwhich electricity can be generated,crops can be cultivated at interspacearea and rainwater can be harvestedfrom top surface of PV-module.About 49% land area of a solarPV-installation system can be used tocultivate crops, which is otherwise leftas fallow. Few of the selected crops aremungbean, mothbean, clusterbean,isabgol, cumin, and chickpea. Apartfrom these, medicinal plants e.g. Aloevera, sonamukhi, sankhpuspi etc. canbe grown. All these crops are generallylow height crops and require lessamount of water and thus are suitablefor AVS. Apart from crop production,about 1,50,000 litre of rainwater onone acre can be harvested. The storedwater can be used as supplementalirrigation to crops during rabi. Annualincome from PV generated electricityhas been estimated as Rupees 7,00,000 peracre, whereas cost involved forinstallation of such system is Rupees55,00,000 and thus the breakevenperiod of the system is about 9-10years.